The Crosstalk Between Signaling Pathways and Cancer Metabolism in Colorectal Cancer - Hon, Kha Wai; Zainal Abidin, Syafiq Asnawi; Othman, Iekhsan; Naidu, Rakesh (Frontiers in Pharmacology, 2021)
Colorectal cancer (CRC) is one of the most frequently diagnosed cancers worldwide. Metabolic reprogramming represents an important cancer hallmark in CRC. Reprogramming core metabolic pathways in cancer cells, such as glycolysis, glutaminolysis, oxidative phosphorylation, and lipid metabolism, is essential to increase energy production and biosynthesis of precursors required to support tumor initiation and progression. Accumulating evidence demonstrates that activation of oncogenes and loss of tumor suppressor genes regulate metabolic reprogramming through the downstream signaling pathways. The crosstalk between signaling pathways and metabolic pathways further facilitates CRC cell proliferation, invasion, and metastasis, leading to cancer progression. This review provides an insight into the crosstalk between signaling pathways and metabolic reprogramming in CRC. Targeting CRC metabolism could open a new avenue for developing CRC therapy by discovering metabolic inhibitors and repurposing protein kinase inhibitors/monoclonal antibodies.